Analisis Formulasi Kebijakan Smart City: (Studi pada Peraturan Bupati No. 13 Tahun 2020 tentang Masterplan Smart City Kabupaten Bojonegoro) - Pangestu, Darmawan Tri (JPAP: Jurnal Penelitian Administrasi Publik, 2023)
The Bojonegoro Regency Government utilizes the momentum of regional development transformation to actualize innovative city-based regional development. The Bojonegoro Regency Government has the opportunity to be part of the “Gerakan Menuju 100 Smart City” program by the Indonesian Ministry of Communication and Information, where selected regions are required to make regulations and formal documents in the form of an intelligent city master plan as the primary reference for implementing innovative city development. Thus, Peraturan Bupati No. 13 tahun 2020 tentang Masterplan Smart City Bojonegoro was formulated. This research aims to systematize the study of the intelligent city policy formulation process as a developing development innovation in Indonesia. This research uses a qualitative case study method by conducting interviews, literature studies and documentation. The findings of this study show that the process of formulating this policy begins with the identification of smart city master plan policy problems that refer to the urgency of strategic issues that need to be resolved according to the regional RPJMD period by taking into account structural, infrastructure and superstructure factors, setting the agenda setting is done by analyzing the existing conditions of business and IT in the region, formulating alternatives to pay attention to how intelligent city readiness is in the area and determining policies based on the results of determining the roadmap and quick-win of medium-term intellectual city development. This research shows that the success of smart city policy formulation, especially in regional head regulations such as this regent regulation, can be determined by the level of coordination maturity between executive government actors. The recommendation for further research is a systematic study of how a policy contained in a regional head regulation can be actively and massively implemented by the various actors and stakeholders involved.